ANALISIS BENTUK DAN MAKNA JAM’ AL TAKSĪR DALAM ALQURAN JUZ 29 DAN 30 (ANALISIS MORFOLOGIS DAN SEMANTIS) - Mudrofin, Mudrofin; Ahmad Hasyim, Mohamad Yusuf; Qutni, Darul (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
Broken plural is one of three plural study of arabic. It has special character whose make it different. Two other plural (intact masculine plural and intact feminine plural) have constant alteration of accidence measure, while it hasn’t. It has complex alteration measure. Alteration of this plural happend through augmentation, elimination, and by changing it’s vowel. Purpose of this research is to know derivate, formation method, and meaning from semantics sector of broken plural on the koran juz 29 and 30. This research is qualitative research with library research design. Data on this research are all of broken plural on the koran juz 29 and 30. Data aggregation of this research use documentation method with data card and recapitulation thread in instrument. Result of this research is from 92 data, 28 data are minor plural, 37 data are major plural, and 27 data are ultimate plural form. Based on semantics, 41 data have constant meaning, 11 data have generalization meaning, 28 data have constrict meaning, and 12 data have changing meaning.